Comparative analysis of fracture resistance and film thickness between flowable composites and resin cement luted lithium disilicate ceramics - Sonjit, Bhornnat; Saikaew, Pipop; Senawongse, Pisol (Mahidol Dental Journal, 2025)
Objectives: This study investigated the fracture resistance and film thickness of the different composite cements that can be used with lithium disilicate-based ceramic restoration (IPS e.max CAD). Materials and Methods: Twenty-five (25) IPS e.max CAD discs (A2, shade HT/C14) with a 10 mm diameter and 1 mm thickness were randomly assigned to five experimental groups (n = 5) according to luting agent G-ænialTM Universal Injectable (GC Corporation, Japan), ClearfilTM AP-X Esthetics FLOW (Kuraray Noritake, Japan), Beautifil injectable X (Shofu Inc., Japan), and FiltekTM Supreme Flowable (3M Oral Care, USA). Flowable composites were bonded between the ceramic disc and dentin. The control group sample was dual-cured resin cement, Multilink N (Ivoclar Vivadent, Liechtenstein). A universal testing machine (Model LR10K; Lloyd Instruments, Fareham, UK) was used to conduct a three-point bending test to determine the fracture resistance. The film thickness was analyzed using scanning electron microscopy (SEM, JSM 6610LV, JEOL, Peabody, PA, USA). The data were analyzed using a one-way ANOVA. Results: Flowable composites presented fracture resistance values comparable to the resin cement, with acceptable film thickness values meeting ISO requirements, except for FiltekTM Supreme Flowable. However, no statistically significant differences were found among groups (p>0.05) Conclusions: Flowable composites could be potential alternatives for ceramic luting, although further studies are needed to confirm their long-term clinical performance.